Cloning and characterization of the first serine carboxypeptidase from a plant parasitic nematode, Radopholus similis - Xin Huang (Nature Portfolio, 2017)
Abstract Radopholus similis is an important parasitic nematode of plants. Serine carboxypeptidases (SCPs) are peptidases that hydrolyse peptides and proteins and play critical roles in the development, invasion, and pathogenesis of certain parasitic nematodes and other animal pathogens. In this study, we obtained the full-length sequence of the SCP gene from R. similis (Rs-scp-1), which is 1665 bp long and includes a 1461-bp open reading frames encoding 486 amino acids with an 18-aa signal peptide. This gene is a double-copy gene in R. similis. Rs-scp-1 was expressed in the procorpus, esophageal glands and intestines of females and in the esophageal glands and intestines of juveniles. Rs-scp-1 expression levels were highest in females, followed by juveniles and males, and lowest in eggs. Rs-scp-1 expression levels were significantly suppressed after R. similis was soaked in Rs-scp-1 dsRNA for 12 h. Nematodes were then inoculated into Anthurium andraeanum after RNAi treatment. Compared with water treatment, R. similis treated with RNAi were reduced in number and pathogenicity. In summary, we obtained the first SCP gene from a plant parasitic nematode and confirmed its role in the parasitic process.